The Morality of Commercial Advertising Broadcast in Indonesian Television According to Islamic Economic Law - Susamto, Burhanuddin; Hakim, M. Aunul; Suwandi, Suwandi; Firdaus, Dwi Hidayatul; Nasyiah, Iffaty (Islamic Family Law Department, Sharia and Law Faculty, Universitas Islam Negeri Ar-Raniry, 2024)
The positive or negative impact of a commercial advertisement on television media depends on the moral quality of the broadcast. This research aims to review the morality of commercial advertising broadcasts on ten Indonesian television stations. To achieve this goal, the author uses empirical legal research with an Islamic economic approach. Data was collected through document studies, namely advertisements on television, journal articles, views of ulama, books and legal regulations. All of the data was then analyzed using quantitative descriptive methods. From data analysis, it is known that the morality of broadcasting commercial advertisements on national television media only achieves a poor rating. This means there are several violations of Islamic economic law in broadcasting commercial advertisements in Indonesia. The most dominant violations are related to low advertising ethics and clothing displays. The fact that many commercial advertisers still behave sensually on television media has the potential to have a negative impact on society. This exploitation has the potential to damage the morality of not only advertisers, but also the public who use television services. To prevent negative impacts, unscrupulous advertising needs to be evaluated by giving warnings and even legal sanctions to advertising service providers. From these findings, the author provides input to advertising service providers to improve morality so that commercial advertising broadcasts do not conflict with Islamic economic law.